Enhancing Poly(3,4-ethylenedioxythiophene) Polystyrene Sulfonate (PEDOT:PSS) Conductivity by Dimethyl Sulfoxide (DMSO) Dopant - Xuan Hao, Nguyen; Nhat Minh, Nguyen; Duc Anh, Ngo; Le Ngoc Thu, Nguyen; Ngoc Duy, Huynh Ha; Gia Man, Nguyen Bui; Nhat Giang, Doan; Hoai Nhan, Luong; Vinh Quang, Dang (VNU Journal of Science: Mathematics - Physics, 2023)
Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), a type of conducting polymer has caught lots of attraction from scientists for its excellent properties as low-cost, non-toxic, etc. This also is a potential material for various applications as transparent electrodes, flexible and stretchable devices, thus improving the electrical properties of this polymer plays an important role. Among various methods such as post-treatment, doping with glycerol, and d-sorbitol herein, DMSO was chosen as an additive to enhance the conductivity of PEDOT:PSS. The results, including the increase in the films conductance according to the rise of DMSO dopant ratio from 0 to 2, good transmittance and surface morphology were clearly presented. This will be the platform for the further study of the utilization of PEDOT:PSS in various potential optoelectronic devices in the future.